Kronisk hjärtsvikt hos katt - Hallberg, Malin (SLU/Dept. of Animal Environment and Health (until 231231), 2010)
This student report is a literature study about cardiac insufficiency in cats and it is written mainly for veterinary nurses. It is about cats with an underlying heart disease that has led to an incompensated heart failure. It presents a general basis on normal anatomy and physiology, and also how to make the diagnosis, therapy and intensive care. The student report is also about the role of the veterinary nurse during the process of the disease, how to help the veterinarian in the best way, how to handle anesthesia in cats with a heart disease, which factors that can have a significant matter in feeding, and what advices to give to a pet owner with a cat with a incompensated heart failure.